Rosellinia qiongensis sp. nov., R. verticillata sp. nov. and a new record of R. lamprostoma from China - Long, Sihan; Pi, Yinhui; Wu, Youpeng; Liu, Lili; Zhang, Xu; Long, Qingde; Lin, Yan; Kang, Yingqian; Kang, Jichuan; Wijayawardene, Nalin N.; Li, Qirui (Phytotaxa, 2022)
Three Rosellinia species were collected from southern China. Based on morphological and phylogenetic analyses, two are introduced as new species while the other is reported as a new record. Rosellinia qiongensis sp. nov. and R. verticillata sp. nov. belong to the R. emergens group. Rosellinia qiongensis differs from its similar species by its dimension of ascospores and three short germ slits on ascospores. Rosellinia verticillata differs from species in this group by its ascospores with whole spore length germ silt and surrounded by a thin slimy sheath. All taxa are made available to illustrations and descriptions.